The Impact of and Barriers to Cardiac Rehabilitation Following Cardiac Surgery in the Adult With Congenital Heart Disease. Issue 2 (March 2022) - Jacobsen, Roni M.; Beacher, Daniel; Beacher, Laura; Earing, Michael G.; Ginde, Salil; Bartz, Peter J.; Cohen, Scott
Abstract : Introduction: There is a paucity of literature evaluating the impact of and barriers to participation in cardiac rehabilitation (CR) in the adult congenital heart disease population. The aims of this study were to evaluate the impact of CR on physical activity and health-related quality of life, as well as to evaluate the barriers to participation in CR in a post-operative adult congenital heart disease population. Methods: Patients ≥18 yr of age seen in the Wisconsin Adult Congenital Heart Disease Program and post–open sternotomy surgery from 2010-2015 were eligible for inclusion. Subjects were mailed a novel physical activity survey and the validated EuroQOL-5D 3L health questionnaire. A retrospective medical record review was performed to extract demographic and clinical data. Results: One hundred thirty-five patients underwent open sternotomy surgery from 2010-2015. Of these, 22 were excluded because of intellectual disability, three opted out, and three survey packets were returned to the sender. A total of 54 of the remaining 107 patients returned completed surveys. Of these, 47 (87%) were referred to CR. Thirty-five patients completed the entire CR program (74%). Those who completed CR were more likely to develop a home/independent exercise program ( P = .027). Barriers to completing CR included insurance coverage, psychiatric disease, and a perception that CR would not be of benefit. Conclusion: Completing CR was associated with developing a home/independent exercise program in post-sternotomy adult patients with congenital heart disease. Barriers to participating in and completing CR in this population could lead to an improved completion rate if modified. Abstract : In a retrospective survey study, completing a cardiac rehabilitation (CR) program was found to be associated with developing a home/independent exercise program in post-sternotomy adults with congenital heart disease. Barriers to completing CR included lack of insurance coverage, psychiatric disease, and a perception that the program would not be beneficial.